2013
DOI: 10.1111/ases.12030
|View full text |Cite
|
Sign up to set email alerts
|

Endo‐laparoscopic approach versus conventional open surgery in the treatment of obstructing left‐sided colon cancer: Long‐term follow‐up of a randomized trial

Abstract: Introduction: We previously conducted a randomized trial comparing the endo-laparoscopic approach (i.e. placing self-expanding metallic stents followed by laparoscopic resection) and conventional open surgery in the treatment of obstructing left-sided colon cancer. This study is a follow-up of the previous randomized trial and aims to report the long-term outcomes of the two groups. Methods: Forty-eight patients from the randomized trial were followed up in an outpatient clinic with regular monitoring. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
5
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 10 publications
5
83
5
3
Order By: Relevance
“…Sabbagh et al 9 showed that overall survival was significantly lower in the SBTS group (25% vs 62%, P Z .0003) and when only patients with no perforation and no metastasis on diagnosis were considered. The studies by Alcántara et al, 19 Tung et al, 27 and Arezzo et al 21 did not confirm these data, however; the meta-analysis by Matsuda et al 28 also showed no significant difference between SBTS and ES in terms of overall survival, disease-free survival, and recurrence. Sloothaak et al, 29 in their analysis of the long-term results of the Stent-in-2 trial, reported that stent placement was associated with a higher risk of recurrence but that the numbers were too small to draw a definitive conclusion.…”
Section: Discussionmentioning
confidence: 95%
“…Sabbagh et al 9 showed that overall survival was significantly lower in the SBTS group (25% vs 62%, P Z .0003) and when only patients with no perforation and no metastasis on diagnosis were considered. The studies by Alcántara et al, 19 Tung et al, 27 and Arezzo et al 21 did not confirm these data, however; the meta-analysis by Matsuda et al 28 also showed no significant difference between SBTS and ES in terms of overall survival, disease-free survival, and recurrence. Sloothaak et al, 29 in their analysis of the long-term results of the Stent-in-2 trial, reported that stent placement was associated with a higher risk of recurrence but that the numbers were too small to draw a definitive conclusion.…”
Section: Discussionmentioning
confidence: 95%
“…En esta serie de casos se logró resecar más de 12 linfonodos en el 100% de nuestros pacientes con una mediana de 41. Existen reportes que han demostrado que transformando la cirugía en electiva de esta manera, se logra recolectar un mayor número de linfonodos, comparado a la cirugía de urgencia 14,18 . Tung y colaboradores presentan una mediana de 23 linfonodos en cirugía con stent versus 11 linfonodos en cirugía de urgencia, con un p significativo 18 .…”
Section: Discussionunclassified
“…Tung y colaboradores en un trabajo prospectivo, randomizado, compararon pacientes estadio II y III, sometidos a resección curativa en cáncer de colon obstructivo, no encontrando diferencias significativas en sobrevida a 5 años al comparar los grupos (42,8% en cirugía de urgencia versus 57,1% en cirugía con stent, con un p = 0,347) 18 . Resultado similar muestra Zhang en su metaanálisis publicado el año 2012, así como un reciente trabajo randomizado múlticéntrico 8,17 .…”
Section: Discussionunclassified
“…15 This guideline is based on the evidence from eight systematic reviews with meta-analysis comparing preoperative stenting with emergency resection for left-sided colonic malignant obstruction, 11,[36][37][38][39][40][41][42] with assimilated data from up to seven RCTs. [43][44][45][46][47][48][49] Three of those RCTs were closed early due to adverse outcomes in the SEMS group (higher 30-day morbidity related to stent perforation), 43,44 or high anastomotic leak rate in the emergency surgery group. 48 The most recently published meta-analysis found that SEMS as a bridge to surgery (n = 195) compared to emergency surgery (n = 187) had a lower overall morbidity (33.1% vs 53.9%, P = 0.03), a higher successful primary anastomosis rate (67.2% vs 55.1%, P < 0.01), and a lower permanent stoma rate (9% vs 27.4%, P < 0.01); however, there was no statistical difference in post-operative mortality (10.7% vs 12.4%).…”
Section: Sems As a Bridge To Elective Surgerymentioning
confidence: 99%